0168 Somatising tendency, occupational strain and musculoskeletal symptoms: results from a longitudinal study among Italian nurses. (23rd June 2014) - Bonzini, Matteo; Bertù, Lorenza; Conti, Marco; D'Amato, Alessia; Veronesi, Giovanni; Coggon, David N; Ferrario, Marco M
Abstract : Objectives: Musculoskeletal symptoms are a common cause of disability, with major impact on workforce wellbeing, absenteeism and productivity. Several, mainly cross-sectional, studies have linked such symptoms to physical workload, and also to psychological and socio-cultural factors. We investigated whether prolonged or increasing job strain, tendency to somatise and other individual characteristics, are associated with worsening musculoskeletal pain. Method: As part of the CUPID study, we investigated a cohort of nurses employed on medical wards at the Varese University Hospitals (Italy). Participants were asked, at baseline and after one year of follow-up, about individual and occupational risk factors, psychological characteristics (including tendency to somatise), occupational strain (by Siegrist's Effort/Reward Imbalance Questionnaire-ERI), and musculoskeletal symptoms. Associations of worsening musculoskeletal pain with perceived job strain were assessed by multivariate log-binomial regression. Results: Occupational stress was associated with pain in the lower back (LBP) and neck/shoulder (NSP) in both cross-sectional questionnaires. Comparing baseline and follow-up answers, workers who reported an increase in perceived stress showed more frequent worsening of both LBP (prevalence of worsening symptoms=41%, OR when compared with not stressed=1.7, 95% CI=1.1–2.7) and NSP (prevalence of worsening=51%, OR=1.2, 95% CI=0.8–1.8). This relationship persisted after adjustment for gender, age and BMI, and exposure to physical workload, and was more evident among subjects with a tendency to somatise (OR=2.8. 95% CI=1.0–7.4 for LBP; OR=1.6, 95% CI=0.8–3.2 for NSP). Conclusions: Our observation suggests that tendency to somatise modifies individual responses to "triggering exposures", such as psychological workload, with important implications for the health, and productivity of workers.